2021
DOI: 10.1080/21711976.2021.1900641
|View full text |Cite
|
Sign up to set email alerts
|

Energy conservation attitudes and intentions: investigating place attachment in Eastern Transylvania, Romania (Actitudes e intenciones respecto al ahorro de energía: investigando el apego al lugar en Transilvania Oriental, Rumanía)

Abstract: This study explores the relationship between place attachment and energy conservation attitudes and behavioural intentions in the Pogány-havas microregion of Romania. Confirmatory factor analysis (CFA) was used to examine three dimensions of place attachment: place identity, place dependence and nature bonding. While place attachment in the region is high, structural equation modelling (SEM) revealed negative links between place dependence and energy conservation attitudes and between place identity and behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
4

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 46 publications
0
3
0
4
Order By: Relevance
“…This was highlighted in studies by Gurney et al (2017), Daryanto and Song (2021) and Klaniecki et al (2021), who showed that the socio-physical bond increases the level of care taken of the surroundings and ecological sustainability. This element also accounts for the lack of local education management and a culture of solid waste exploitation, which ends up affecting the health of the communities and reinforcing the poor image of the place.…”
Section: Negligent Governments Fragile Attachmentsmentioning
confidence: 94%
See 4 more Smart Citations
“…This was highlighted in studies by Gurney et al (2017), Daryanto and Song (2021) and Klaniecki et al (2021), who showed that the socio-physical bond increases the level of care taken of the surroundings and ecological sustainability. This element also accounts for the lack of local education management and a culture of solid waste exploitation, which ends up affecting the health of the communities and reinforcing the poor image of the place.…”
Section: Negligent Governments Fragile Attachmentsmentioning
confidence: 94%
“…La extensa trayectoria que posee la psicología ambiental explorando los vínculos socio físicos, ha permitido reconocer que el apego al lugar es complejo y multicausal. Este concepto, que hace referencia a la conexión emocional que desarrollan las personas con los espacios (Hernández, 2021;Hernández et al, 2014) tradicionalmente, se ha empleado para comprender los comportamientos proambientales (Daryanto & Song, 2021;Gifford, 2014;Gurney et al, 2017;Klaniecki et al, 2021) y la satisfacción residencial (Duque-Calvache et al, 2017;Málovics et al, 2019;Sharp, 2019;Von Breymann, 2019). En estos estudios se ha encontrado que el apego al lugar puede incrementar la presencia de conductas ecológicamente responsables (Gurney et al, 2017;Klaniecki et al, 2021), la implicación en procesos organizativos y el sentido de comunidad (aunque los resultados no son consistentes en culturas colectivistas y áreas rurales donde es más común el apego al lugar en comparación a culturas individuales y áreas urbanas; Daryanto & Song, 2021;Hernández, 2021).…”
Section: Apego Al Lugar En Contextos Estigmatizados: Un Estudio Desde...unclassified
See 3 more Smart Citations